STYLUS PROFILOMETRY IN SURFACE ROUGHNESS MEASUREMENTS OF THE VERTICAL CONICAL MIXING UNIT USED IN A FOOD INDUSTRY (Journal of Mechanical Engineering, 2018)
In the paper, use of stylus profilometry technique in measurements of surface roughness parameters of technological equipment used in the food industry has been demonstrated. The assessment of internal surfaces of the vertical conical mixing unit and its components was carried out by the use of stylus instrument Hommel-Tester T-8000 supported bythe HommelMap Basic 3.1 software. The obtained values of selected roughness (profile) parameters (Ra, Rq, Rp, Rv and Rz) as well as results of the others carried out analysis (Abbott-Firestone curves, graphical studies of Sk parameters) confirmed the correctness of machining process of the assessed surfaces, despite fact, that measurement process were complicated dueto their large size and weight.